Acute Toxicity of Convolvulus Arvensis in Mice and its Mechanism of Spasmolysis on Rabbit Jejunum - Khalil, Saif Ullah Khan (International Journal of Pathology, 2022)
Introduction: Convolvulus arvensis has contrasting results reflecting both the spasmolytic as well as the spasmogenic properties according to studies. It may be because of a wide variety of chemical ingredients in the plants. In addition the mechanism of the effect and the safe therapeutic dose is not clearly understood. Objective: The current study is designed to investigate Convolvulus arvensis for the possible antispasmodic activity of the plant extract. Material and Methods: An experimental study was performed for 24 hours in Khyber medical university. Acute toxicity was tested on mice using Lorke’s model. 8 groups were made out of which 1 served as a negative control group. Extract of C. arvensis was administered through intraperitoneal route (i.p). Secondly antispasmodic effect of on spontaneous rabbits’ jejunal contractions was performed, followed by testing of Antispasmodic effect of on atropine pretreated and KCl-induced jejunal preparations of rabbits respectively. Results: Extract of C. arvensis is safe up to 500 mg/kg in experimental animals. Furthermore cumulative addition of crude methanolic extract of C. arvensis caused concentration-dependent inhibition in low KCl and high KCl induced contractions. The EC50 for the effect of crude methanolic extract of C. arvensis on low KCl induced contraction without glibenclamide was (1.79 ± 0.11 mg/mL). The EC50 value for the effect of crude methanolic extract of C. arvensis on low KCl in the presence of glibenclamide (3 µM) was (2.85±0.12 mg/mL). Conclusion: The observed spasmolytic activity of extract of C. arvensis is through K+ channel activation as well as activation of muscarinic receptors. The crude extract is safe up to 500 mg/kg.